Assessing AI-Assisted Translation Competency Among Development Economics Students - Adys, Himaya Praptani; Adys, Himala Praptami; Usman, Misnawaty (Ma Chung Press, 2025)
This research examines the translation capabilities of development economics students at Universitas Negeri Makassar when employing artificial intelligence-based translation tools for economic literature. As AI technology becomes increasingly prevalent in academic and professional environments, evaluating students' proficiency in utilizing these technological resources has emerged as essential for educational strategy formulation and skill enhancement initiatives. A quantitative survey methodology was implemented involving 107 students from the development economics program to measure translation precision, operational efficiency, and analytical assessment abilities during AI-supported translation processes. The findings indicate considerable disparities in skill levels, whereby students exhibited superior competence in fundamental translation activities while encountering difficulties with sophisticated economic vocabulary and contextual subtleties. The outcomes demonstrate that although AI-powered tools improve translation velocity and resource availability, systematic instructional frameworks are required to optimize their pedagogical value. This investigation adds to the expanding scholarly discourse on AI incorporation within translation pedagogy and offers actionable insights for academic program enhancement in economics education.